METODE ASM PADA MASALAH TRANSPORTASI SEIMBANG - Septiana, Arum Ryani; Solikhin, Solikhin; Ratnasari, Lucia (MATEMATIKA, 2017)
The transportation problem is special case on the linear programming which examines the goods’ distribution for minimize shipping cost or maximize profits. In general, transportation problem requires two stages of completion, which is looking for feasible solution first and the look for the optimal solution. Abdul Quddoos, Dr. Shakeel Javaid, and Prof. Mohd Masood Khalid did some research for a new method, ASM method which is direct method with simple and fast way. This method relies on the cell that has the number 0 with the smallest index, and used to minimize transport costs. This final project determines the optimal solution using ASM method, both to mimize costs and maximize profits, and investigate the optimal method of ASM. The solution that obtained by ASM method on balanced transportation problem is always optimal, while for unbalanced transportation problem is not always optimal. The difference between algorithm for minimizing cases and maximize cases lies only in the first step, which is if the maximization case, then change c_ij into(-c_ij ).